Pengembangan bahan ajar elektronik flipbook dalam Pembelajaran Seni Rupa Daerah siswa kelas V di Sekolah Dasar - Zeni Rahma Dayanti (IKIP Siliwangi, 2021)
AbstrakThis research was conducted to solve problems regarding children's difficulties in learning regional art in class V by using flipbook-based teaching materials and to increase teacher creativity in making electronic-based teaching materials. The purpose of this research is to design flipbook-based digital teaching materials to facilitate learning of regional art, especially class V. The method used is Design Based Research (DBR) starting from analyzing needs according to problem identification and exploring what is found in elementary schools, design and construction. tools developed, to evaluation and reflection of the developed tools. The results of electronic flipbook teaching materials in regional art learning developed by researchers in grade 5 elementary schools include: (1) understanding of regional art, (2) kinds of regional art, (3) characteristics of regional art, (4) the function of regional art. By doing validation from experts so that flipbook-based electronic teaching materials in art learning developed by researchers are feasible to use. In this way, flipbook electronic teaching materials can meet the needs of regional art learning in elementary schools because there are multimedia such as animation, images, videos or audio so that learning can be supportive and more interesting by utilizing the sophistication of existing technology. In the position of this electronic teaching material as an additional reference in art learning in elementary schools.Keywords: Elektronic Teaching Materials, Flipbooks, Regional ArtsPenelitian ini dilakukan untuk memecahkan masalah mengenai kesulitan anak dalam pembelajaran seni rupa daerah di kelas V dengan menggunakan bahan ajar berbasis flipbook serta meningkatkan kreativitas guru dalam membuat bahan ajar berbasis elektronik. tujuan dari penelitian ini untuk mendesain produk bahan ajar digital berbasis flipbook untuk memfasilitasi pembelajaran seni rupa daerah khususnya kelas V. metode yang digunakan adalah Design Based Research (DBR) dimulai dari menganalisis kebutuhan sesuai indetifikasi masalah dan mengeksplor apa yang ditemukan disekolah dasar, desain dan konstruksi perangkat yang dikembangkan, sampai evaluasi dan refleksi perangkat yang dikembangkan. Hasil dari bahan ajar elektronik flipbook dalam pembelajaran seni rupa daerah yang dikembangkan oleh peneliti di kelas V sekolah dasar diantaranya: (1) pengertian seni rupa daerah, (2) Macam-macam seni rupa daerah, (3) ciri-ciri seni rupa daerah, (4) fungsi seni rupa daerah. Dengan melakukan validasi dari para ahli sehingga bahan ajar berbasis elektronik flipbook dalam pembelajaran seni rupa yang dikembangkan peneliti layak untuk digunakan. Dengan begitu, bahan ajar elektronik flipbook bisa memenuhi kebutuhan pembelajaran seni rupa daerah di sekolah dasar karena terdapat multimedia seperti animasi, gambar, video atau audio agar pembelajaran dapat mendukung dan lebih menarik dengan memanfaatkan kecanggihan teknologi yang ada. Pada posisi bahan ajar elektronik ini sebagai referensi tambahan dalam pembelajaran seni di sekolah dasar.Kata Kunci: Bahan Ajar Elektronik, Flipbook, Seni Rupa Daerah